Anesthetic complications including two cases of postoperative respiratory depression in living liver donor surgery - David Beebe; Harpreet Singh; John Jochman; Paul Luikart; Ranier Gruessner; Angelica Gruessner; Kumar Belani (Wolters Kluwer Medknow Publications, 2011)
Background: Living liver donation is becoming a more common means to treat patients with liver failure because of a shortage of cadaveric organs and tissues. There is a potential for morbidity and mortality, however, in patients who donate a portion of their liver. The purpose of this study is to identify anesthetic complications and morbidity resulting from living liver donor surgery. Patients and Methods: The anesthetic records of all patients who donated a segment of their liver between January 1997 and January 2006 at University of Minnesota Medical Center-Fairview were retrospectively reviewed. The surgical and anesthesia time, blood loss, hospitalization length, complications, morbidity, and mortality were recorded. Data were reported as absolute values, mean ± SD, or percentage. Significance (P < 0.05) was determined using Student's paired t tests. Results: Seventy-four patients (34 male, 40 female, mean age = 35.5 ± 9.8 years) donated a portion of their liver and were reviewed in the study. Fifty-seven patients (77%) donated the right hepatic lobe, while 17 (23%) donated a left hepatic segment. The average surgical time for all patients was 7.8 ± 1.5 hours, the anesthesia time was 9.0 ± 1.3 hours, and the blood loss was 423 ± 253 ml. Forty-six patients (62.2%) received autologous blood either from a cell saver or at the end of surgery following acute, normovolemic hemodilution, but none required an allogenic transfusion. Two patients were admitted to the intensive care unit due to respiratory depression. Both patients donated their right hepatic lobe. One required reintubation in the recovery room and remained intubated overnight. The other was extubated but required observation in the intensive care unit for a low respiratory rate. Twelve patients (16.2%) had complaints of nausea, and two reported nausea with vomiting during their hospital stay. There were four patients who developed complications related to positioning during the surgery: Two patients complained of numbness and tingling in the hands which resolved within two days, one patient reported a blister on the hand, and one patient complained of right elbow pain that resolved quickly. Postoperative hospitalization averaged 7.4 ± 1.5 days. There was no patient mortality. Discussion: Living liver donation can be performed with low morbidity. However, postoperative respiratory depression is a concern and is perhaps due to altered metabolism of administered narcotics and anesthetic agents.